Awareness of idiopathic intracranial hypertension in children among pediatricians in Saudi Arabia: a cross-sectional study - Al-Omari, Mohammed A.; AlShammari, Ahmad A.; Shash, Hwazen A.; Almutairi, Abdullah K.; AlQahtani, Fai A.; AlAttas, Razan H.; AlNaimi, Somyyah I.; AlAmmari, Alia M.; Almobarak, Sulaiman (Frontiers in Pediatrics, 2025)
BackgroundIdiopathic intracranial hypertension (IIH) is a rare condition in children, often underdiagnosed due to its rarity and non-specific clinical presentations. This study aimed to assess the awareness and knowledge of pediatricians in Saudi Arabia regarding IIH in the pediatric population.MethodsA nationwide cross-sectional study was conducted using a validated electronic questionnaire distributed to registered pediatricians across various subspecialties. The questionnaire assessed knowledge on IIH definition, clinical presentation, diagnosis, management, and prognosis. Participants were categorized by years of experience into: Group A (1–9 years) and Group B (≥10 years). Responses between the two groups were compared.ResultsA total of 234 pediatricians completed the questionnaire (Group A: 43%, n = 101; Group B: 57%, n = 133). The overall knowledge level was moderate, with a correct response rate of 73%. While most respondents demonstrated understanding of IIH definitions and risk factors, knowledge gaps were noted in incidence, diagnostic criteria, and management. Pediatricians in Group B were significantly more likely to recognize headache as the most common symptom (p = 0.003) and the importance of a multidisciplinary approach to management (p = 0.001).ConclusionThe study identified significant knowledge gaps among pediatricians regarding IIH in children, particularly among those with fewer years of clinical experience. Addressing these gaps through targeted educational programs is essential to enhance early recognition, accurate diagnosis, and effective management of pediatric IIH, ultimately reducing the risk of serious complications such as irreversible vision loss.